Mossbauer Spectroscopy : Applications in Chemistry, Biology, Industry, and Nanotechnology. - Sharma, Virender K. (Wiley, 2013)
Providing a modern update of the field, Mossbauer Spectroscopy focuses on applications across a broad range of fields, including analysis of inorganic elements, nanoparticles, metalloenzymyes, biomolecules (including proteins), glass, coal, and iron. Ideal for a broad range of scientists, this one-stop reference presents advances gained in the field over past two decades, including a detailed theoretical description of Mossbauer spectroscopy, an extensive treatment of Mossbauer spectroscopy in applied areas, and challenges and future opportunities for the further development of this tec.